AUTOLOGOUS MESENCHYMAL STEM CELL TRACKING IN THE PRESENCE OF ISCHEMIC STROKE IN RATS - Торяник, І.І.; Колесник, В.В. (World of Medicine and Biology, 2014)
The authours of the article analyse possibilities and prospects of autologous mesinchymal stem cell traking usage (AMSC) in the research of effectiveness taken as related to cell therapy in the experiment. To accomplish this three month old male Wistar line rats with simulated ischemic embolic stroke (under functional blood flow) were used. On the 1-st, 3-rd, 7-th, 14-th days of didease endovenous, intracranial, suboccipital AMSC suspension was injected to them. The attendance was pursued for 28 days. The analysis of the results was performed using the range and resourses of modern luminescent microscopy. The registration of the reactivation processes (reparative and regenerative reactions) took place considering the rate of zonal congestion mobility of luminescent РКН 26 dye and futher changes of glow intensity, in-touch capabilities of taken medication. Summing up, the authors emphathise that AMSC tracking is the indicator of the effectiveness of the transplantation undertaken; the main condition for its realisation is the presence of organic matter injuries in one of existing types of tissue (in our case, nerve tissue); qualitative AMSC definition is possible only by means of their detection by РКН 26 vital stain dying and further light-optical analysis of medications.